Rerefinement of the co-crystal of 4-hydroxypyridine with 4-hydroxypyridinium nitrate - Gao, S.; Ng, S.W.; Zain, Sharifuddin Md; Huo, L.H.; Lu, Z.Z. (International Union of Crystallography, 2004)
The crystal structure of the title salt adduct, C5H6NO+.NO3-.C5H5NO, has a C5H6NO+/ C5HNO cation/ molecule assembly ( which lies on an inversion center) whose components are linked through their O atoms by a short hydrogen bond [2.446 (3) Angstrom]. The cation is formally the 4-hydroxypyridinium cation and the neutral component the 4-pyridinone molecule, but the two could not be differentiated as they occupy equivalent positions, with the H atom disordered between them. The nitrogen-bound H atom interacts with the nitrate ion [2.840 ( 1) Angstrom], which lies on another special position of site symmetry 2.